Implementation of Inventory System by P (R, T) Model with Differenced Time of Known Priced Increase at PT Inti Vulkatama - Y.M Kinley Aritonang; Carles Sitompul; Alfian Alfian (Research Report - Engineering Science, 2014)
PT IntiVulkatama is a manufacturing company forthe tire retreading. The demand of the product is probabilistic causing the PT IntiVulkatama often experience shortages of raw material inventory (backorder) that could produce the company to lose the trust of its customers. Currently, PT IntiVulkatama address this problem using a forecasting method by looking at the demand of the past. PT IntiVulkatama must have a better inventory system that can minimize the expected total cost especially when facing the condition of differenced time of known priced increase for some of the raw materials.It is suggested that a good method for solving the problem is fixed order interval system. With this system, PT IntiVulkatama can perform a joint order with a certain time interval and the order size is adjusted to the difference between the maximum inventory and the amount of stock that is available when the order is made. In addition, PT IntiVulkatama should able to determine the sixe of special order when one or some of raw materials experiencing the differenced time of known priced increase for two raw materials.Based on data, PT IntiVulkatama should make a joint order for its six raw materials with a time interval of 1.12 weekwith each order size reaches the maximum of the inventory. The result of the price increase problem is a method of the differenced time of known priced increase with the savings value greater than zero. The study results in a recommendation that not to perform a special order due to the saving is less than the total cost.